2021
DOI: 10.1152/ajpendo.00623.2020
|View full text |Cite
|
Sign up to set email alerts
|

Reduced glucose-stimulated insulin secretion following a 1-wk IGF-1 infusion in late gestation fetal sheep is due to an intrinsic islet defect

Abstract: Insulin and insulin-like growth factor-1 (IGF-1) are fetal hormones critical to establishing normal fetal growth. Experimentally elevated IGF-1 concentrations during late gestation increase fetal weight but lower fetal plasma insulin concentrations. We therefore hypothesized that infusion of an IGF-1 analog for one week into late gestation fetal sheep would attenuate fetal glucose-stimulated insulin secretion (GSIS) and insulin secretion in islets isolated from these fetuses. Late gestation fetal sheep receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 59 publications
1
21
2
Order By: Relevance
“…In this study, we demonstrated that oIGF-1, like LR3 IGF-1 ( Stremming et al, 2021 ), increased in vitro myoblast proliferation, in vivo myoblast proliferation, and selective fetal organ weight, but it did not increase fetal body weight. Similar to infusion of LR3 IGF-1, fetal oIGF-1 infusion for 1 week also attenuated fetal insulin concentrations, which has been previously reported ( Liechty et al, 1996 ; Lok et al, 1996 ; Boyle et al, 1998 ; White et al, 2018 ; Stremming et al, 2021 ; White et al, 2021 ); however, fetal glucose concentrations in oIGF-1 are maintained similar to control animals. Fetal plasma amino acid concentrations were also lower after infusion of oIGF-1, which is consistent with infusion of LR3 IGF-1 ( Stremming et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In this study, we demonstrated that oIGF-1, like LR3 IGF-1 ( Stremming et al, 2021 ), increased in vitro myoblast proliferation, in vivo myoblast proliferation, and selective fetal organ weight, but it did not increase fetal body weight. Similar to infusion of LR3 IGF-1, fetal oIGF-1 infusion for 1 week also attenuated fetal insulin concentrations, which has been previously reported ( Liechty et al, 1996 ; Lok et al, 1996 ; Boyle et al, 1998 ; White et al, 2018 ; Stremming et al, 2021 ; White et al, 2021 ); however, fetal glucose concentrations in oIGF-1 are maintained similar to control animals. Fetal plasma amino acid concentrations were also lower after infusion of oIGF-1, which is consistent with infusion of LR3 IGF-1 ( Stremming et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
“…At the end of the infusion period, fetal IGF-1 concentrations were 3.5-fold higher in oIGF-1 infused fetuses compared to saline infused fetuses ( Figure 3B ). Because IGF-1 infusion decreases fetal insulin concentrations ( Liechty et al, 1996 ; Lok et al, 1996 ; Boyle et al, 1998 ; White et al, 2018 ; Stremming et al, 2021 ; White et al, 2021 ), plasma insulin concentrations were obtained. At the end of the infusion period, fetal plasma insulin concentrations were 89% lower in oIGF-1 infused fetuses compared to fetuses that received a saline infusion ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations